Validation of Droplet Digital Polymerase Chain Reaction for Salmonella spp. Quantification - Villamil, Carolina; Calderon, Martha Nancy; Arias, Maria Mercedes; Leguizamon, John Emerson (Frontiers in Microbiology, 2020)
Salmonellosis is a foodborne disease produced by Salmonella spp., although cell culture is the gold standard method for its identification, validated molecular methods are becoming an alternative, because of their rapidity, selectivity and specificity. A simplex and duplex droplet digital polymerase chain reaction (PCR)-based method for the identification and quantification of Salmonella using ttr, invA, hilA, spaQ, and siiA gene sequences was validated. The method has high specificity, working interval between 8 to 8000 cp/µL in reaction, limit of detection of 0.5 copies/µL, and precision ranging between 5% and 10% measured as a repeatability standard deviation. The relative standard measurement uncertainty was between 2 to 9%. This tool will improve food safety in national consumption products and will increase the competitiveness in agricultural product trade.